Who has special needs? - Campos, Valeria (Journal of Oral Research, 2019)
What does it mean to be special? For some time now, as I have been more involved in the lives of persons with disabilities (PwD) in a social context, and not only from a healthcare perspective, I have been struggling with the euphemism “special needs”. The euphemism “special needs” appears to convey people who need different things from the rest of the population.